Discovery of new benzensulfonamide derivatives as tripedal STAT3 inhibitors - Guo, Jianpeng; Yu, Wenying; Cai, Guiping; Zhang, Wenda; Li, Shanshan; Zhu, Jiawen; Song, Dongmei; Kong, Lingyi (European journal of medicinal chemistry, 2018)
Persistent activated STAT3 has a striking correlation with cancer development and inhibition of STAT3 signaling pathway is a novel therapeutic way for human cancers. Among STAT family, STAT1 and STAT3 play opposite roles in tumorigenesis. However, the discovery of selective STAT3 inhibitors is still challenging to date. In this study, a series of small-molecular (MW < 500) benzensulfanilamide derivatives were designed to selectively suppress STAT3 activation for anti-cancer treatment. The most potent compound 11 inhibited both overexpressed and IL-6 induced STAT3 phosphorylation, whereas 11 displayed little effect on the phosphorylation of other STAT isoforms STAT1, STAT5, demonstrating 11 was a selective STAT3 inhibitor. Meanwhile, 11 dismissed STAT3 DNA binding activity and colony formation. In addition, 11 elevated the ROS level and induced apoptosis of cancer cells. Furthermore, 11 effectively suppressed tumor growth in an in vivo mouse-xenograft model. Compound 11 selectively inhibited STAT3 activation to exert antitumor activity. [Display omitted] •Novel benzensulfonamide derivatives were discovered as STAT3 inhibitors.•11 selectively inhibited STAT3 phosphorylation among other STAT isoforms.•11 exhibited potent antitumor activity in vitro.•11 arrested tumor growth in vivo.